Undoubtedly Things do not Start; Or They Do Not Start When They Are Invented. Or the World Was Invented Old. - Gris, Juan (En-Claves del Pensamiento, 2015)
Obra reseñada: Idalia Sautto. Una vida tan llena de esdrújulas. México, Torres Asociados, 2007. ISBN: 970-9066-49-8.